Combined toxic effects of nitrite and ammonia on life history traits of Daphnia pulex - Yu, Bo; Lyu, Kai; Li, Jiajia; Yang, Zhou; Sun, Yunfei (Frontiers in Environmental Science, 2022)
Nitrite and ammonia are two of the most common toxic nitrogenous pollutants in aquatic ecosystem, which can pose a serious threat to the health of aquatic organisms. Cladocerans, as an important part of freshwater ecosystem, will inevitably be harmed by these pollutants. To evaluate the combined toxic effects of these nitrogenous pollutants on cladocerans, we simulated 15 combinations of five nitrite concentrations (0, 0.5, 2, 4, 8 mg L-1) and three ammonia concentrations (0, 0.1, 1 mg L-1) to study the changes of life history traits of Daphnia pulex exposed to these combinations for 21 days. Results showed that under the combined stress of nitrite and ammonia, the survival time of D. pulex was shortened, the time to first batch of eggs and time to first brood were delayed, the body size and tail spine length at maturation were reduced, and the total offspring and the number of broods were decreased. There were some synergistically negative effects between the two nitrogenous pollutants. The presence of ammonia reduced the tolerance of D. pulex to nitrite, and vice versa. These findings provided new insights into the combined toxic effects of nitrite and ammonia on the life history traits of cladocerans, and were of great significance for understanding the population dynamics of specific species in cladocerans community under the condition of compound nitrogenous pollutants.